2022
DOI: 10.1002/admi.202200503
|View full text |Cite
|
Sign up to set email alerts
|

High‐Quality Monolayer Reduced Graphene Oxide Films via Combined Chemical Reduction and Ethanol‐Assisted Defect Restoration

Abstract: at a low cost is another advantage in using GO for such applications. [10] However, the oxygen functional groups and lattice vacancies present in GO are accountable for opening up a large bandgap in the graphene lattice, which makes it electrically insulating. [11] Many deoxygenation or reduction strategies have been established to improve the graphitic structure and the electrical conductivity in GO, yet its quality is inferior to pristine or chemical vapor deposition (CVD) grown graphene. Chemical reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In the N 1s spectra (Figures c and S7b), two peaks appear at 398.1 and 399.2 eV, corresponding to N–B and N–H bonds, respectively. The peak at 284.5 eV is attributed to sp 2 (CC), while the peak at 288.6 eV can be assigned to CO (Figures d and S8c). The C–O peak on GO is higher than that on RGO, which is evident in the heat reduction under N 2 /H 2 (Figure S8). In the O 1s deconvolution spectra (Figures e and S8d), the large peak at 532.5 eV is assigned to C–O and the weak peak at 533.6 eV could be attributed to an O–C–O …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the N 1s spectra (Figures c and S7b), two peaks appear at 398.1 and 399.2 eV, corresponding to N–B and N–H bonds, respectively. The peak at 284.5 eV is attributed to sp 2 (CC), while the peak at 288.6 eV can be assigned to CO (Figures d and S8c). The C–O peak on GO is higher than that on RGO, which is evident in the heat reduction under N 2 /H 2 (Figure S8). In the O 1s deconvolution spectra (Figures e and S8d), the large peak at 532.5 eV is assigned to C–O and the weak peak at 533.6 eV could be attributed to an O–C–O …”
Section: Resultsmentioning
confidence: 94%
“…The modified Hummers’ method was used to synthesize graphene oxide (GO), 31 , 32 and the reduced graphene oxide (RGO) film was prepared according to our previous report. 33 In detail, the SiO 2 /Si substrate was cleaned with acetone and distilled water, followed by UV–O 3 plasma treatment (TC-003, Meiwafosis.Co., Ltd.), which was performed to remove all chemical residues and improve the hydrophilicity. GO was dispersed in DMF (1 mg/mL), followed by ultrasonication and centrifugation, which were performed several times to remove bulk GO flakes.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Wei et al 15 found that multistep reduction of GO was more effective compared to the single-step process. For instance, De Silva et al 16 employed a mixture of hydroiodic acid and trifluoroacetic acid followed by thermal reduction with ethanol to obtain high-quality RGO of as low as 0.46 kΩ sq −1 sheet resistance. Nevertheless, the second step reduction was carried out at an elevated temperature of 800 °C for 30 minutes, limiting the practicality and scalability of the method.…”
Section: Introductionmentioning
confidence: 99%